Updating regionalization of precipitation in Ecuador - Ilbay-Yupa, Mercy (2021)
This article identifies homogeneous precipitation regions in Ecuador and their relationship to the El Niño-Southern Oscillation (ENSO), using monthly records from 215 rain stations for the 1968–2014 period. A k-means clustering analysis was used to divide the study area into k regions based on monthly and annual precipitation variables and geographic location (latitude, longitude, and altitude). The robustness of each cluster was evaluated using the “silhouette” coefficient. The groupings were then validated using the regional vector method (RVM). Twenty-two regions of homogeneous precipitation were identified. Seven regions are related to regional climate processes on the Pacific coast (unimodal precipitation). Two regions in the western foothills of the Andes show significant orographic rainfall. Eight regions in the inter-Andean region present a bimodal precipitation regime characterized by a reduction of precipitation from north to south and local variability. Five regions were identified in the Amazon area: three on the outer flanks of the eastern mountain range, one sub-Andean area, and one in the Amazon plain with regular rainfall throughout the year, influenced by the Amazon basin. Although Tropical Pacific sea surface temperature (SST) is strongly related to precipitation in the coastal regions of Ecuador, our findings indicate that SST influence varies among the regions of the country because Ecuador is influenced by the modes of precipitation variability in Colombia and Peru.